Transcatheter aortic valve implantation in situs inversus totalis - Dubois, Christophe L. (Oxford University Press, 2012)
A frail 84-year old lady with situs inversus totalis and symptomatic aortic stenosis underwent a successful transcatheter aortic valve implantation (TAVI) after extensive diagnostic work-up. We show illustrative pre- and postintervention three-dimensional reconstruction imaging and describe how conventional and dedicated imaging software can support the planning and performance of TAVI.